Intramuscular Expression of Plasmid-Encoded FVII-Fc Immunoconjugate for Tumor Immunotherapy by Targeting Tumoral Blood Vessels and Cells - Ma, Liping; Wang, Guanru; Liu, Sijia; Bi, Feng; Liu, Ming; Wang, Gang (Frontiers in Oncology, 2021)
Tissue factor (TF) has been confirmed to be specifically expressed by vascular endothelial cells (VECs) in solid tumors and certain types of malignant tumor cells. Coagulation factor VII (FVII) can specifically bind to TF with high affinity, so the FVII-TF interaction provides an ideal target for tumor therapy. Expression of proteins in skeletal muscles is a simple and economical avenue for continuous production of therapeutic molecules. However, it is difficult to treat solid tumors till now due to the limited number of therapeutic proteins produced by the intramuscular gene expression system. Herein, we strived to explore whether anti-tumor effects can be achieved via intramuscular delivery of a plasmid encoding a FVII-guided immunoconjugate (Icon) molecule by a previously established Pluronic L64/electropulse (L/E) technique. Our study exhibited several interesting outcomes. 1) The mouse light chain of FVII (mLFVII) molecule could guide red fluorescent protein (RFP) to accumulate predominantly at tumor sites in a TF-dependent manner. 2) Intramuscular expression of mLFVII-hFc (human IgG1 Fc) Icon could significantly inhibit the growth of both liver and lung cancers in nude mice, and the inhibition extent was proportional to the level of tumor-expressed TF. 3) The number of blood vessels and the amount of blood flow in tumors were significantly decreased in mLFVII-hFc Icon-treated mice. 4) This immunotherapy system did not display obvious side effects. Our study provided an efficient and economical system for tumor immunotherapy by targeting both blood vessels and tumor cells. It is also an open system for synergistic therapy by conveniently integrating other anticancer regimens.